Distributed energy system selection for a commercial building by using Multi Criteria Decision Making methods. (22nd October 2022) - Dagtekin, Yilmaz; Kaya, Serkan; Besli, Nurettin
Abstract: Turkiye has made a significant progress in liberalizing electricity generation, transmission and distribution systems. Utilization of Distributed Generation systems are encouraged to contribute to this liberalization process. It is a complex problem for the consumer to choose an appropriate combination of Distributed Generation systems. This complexity arises from the differences among the characteristics of Distributed Generation systems such as investment cost, operating cost, carbon emissions, primary energy consumption and primary energy utilization rate. Therefore, Distributed Generation system selection problem emerges as a multi criteria decision making problem. Finding the optimal alternative for many conflicting and interacting criteria can be achived by Multi Criteria Decision Making methods. In this study, the problem of choosing the most suitable alternative among 7 available Distributed Generation systems for a commercial building, which is a real-world problem, is discussed. First of all, 5 criteria were determined by considering the opinions of 23 experts in the field and the studies in the literature. The AHP method was used to weight the criteria according to 6 scenarios. Alternatives were ranked by using 6 Multi Criteria Decision Making methods (AHP, ANP, TOPSIS, ELECTRE, PROMETHEE, VIKOR). Spearman correlation analysis was performed in pairs on all 6 rankings for each scenario in order to identify which ranking is correct and the final ranking table was formed. The results showed that the criteria whose weights changed as a result of the scenarios according to the local conditions had an effect on the selection of the Distributed Generation system. In addition, the final ranking can be formed more accurately by performing correlation analysis of the rankings by using different multi criteria decision making methods. Highlights: The selection problem of DG sources for a commercial building, which is very limited in the literature, is discussed. While maximum 3 methods are used for the selection of DG systems in the literature, 6 methods are used in this study. Statistical analysis was made on the results obtained with 6 Methods according to 6 scenarios. Real-world problem for a commercial building has been solved. Thus, the operating cost has been reduced.